Arteriovenous Malformation (AVM) of Left Frontal Lobe: A Case Report (Journal of National Institute of Neurosciences Bangladesh, 2018)
Arteriovenous malformation (AVM) is a rare congenital condition of the brain. In majority of cases AVMs remain asymptomatic and silent till it ruptures. But it can be a cause of cerebral haemorrhage, stroke, seizures, moderate to severe headache, loss of vision, aphasia, numbness or weakness of limbs. In current study, revealed a 25 years age patient of AVM admitted in Department of Neurosurgery at National Institute of Neurosciences (NINS) on December, 2013 with the complaints of loss of consciousness two times before admission, history of generalized seizure started over left side, headache for 2 years and vertigo for 1 year. Following admission the patient was evaluated clinically including all neurological examinations. All routine investigations were done. The patient was further evaluated by MRI, CT scan, CTA. Arteriovenous malformation was found in left frontal region. Under G/A nidus was excised totally in a single mass. Post MRI had shown the total removal of the AVM. Histopathological findings also revealed arteriovenous malformations. The post-operative period was uneventful and patient improved satisfactorily. He was found neurologically stable in follow up after 3 months. These researchers reported this case for its rarity and effective diagnosis and treatment by surgery.Journal of National Institute of Neurosciences Bangladesh, 2017;3(1): 62-66